2019
DOI: 10.3390/ijms20030511
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Physical Activity as a Prevention Method for Knee Osteoarthritis and the Role of Synoviocytes as Biological Key

Abstract: The purpose of this study was to investigate the influence of moderate physical activity (MPA) on the expression of osteoarthritis (OA)-related (IL-1β, IL-6, TNF-α, MMP-13) and anti-inflammatory and chondroprotective (IL-4, IL-10, lubricin) biomarkers in the synovium of an OA-induced rat model. A total of 32 rats were divided into four groups: Control rats (Group 1); rats performing MPA (Group 2); anterior cruciate ligament transection (ACLT)-rats with OA (Group 3); and, ACLT-rats performing MPA (Group 4). Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
135
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(141 citation statements)
references
References 53 publications
(80 reference statements)
3
135
1
2
Order By: Relevance
“…This indicates a beneficial effect of MPA on the synovium likely by rescuing type B synoviocyte dysfunction at the early stages of OA. Yet, pro‐inflammatory cytokine IL‐6 expression in ACLT‐rats performing MPA did not decrease with physical activity. Likewise, Cifuentes et al reported that 8 weeks of running at 13 m/min significantly decreased the oxidative stress markers in OA‐affected joints.…”
Section: The Exercise Effect On Cartilage Bio‐composition and Morpholmentioning
confidence: 97%
See 3 more Smart Citations
“…This indicates a beneficial effect of MPA on the synovium likely by rescuing type B synoviocyte dysfunction at the early stages of OA. Yet, pro‐inflammatory cytokine IL‐6 expression in ACLT‐rats performing MPA did not decrease with physical activity. Likewise, Cifuentes et al reported that 8 weeks of running at 13 m/min significantly decreased the oxidative stress markers in OA‐affected joints.…”
Section: The Exercise Effect On Cartilage Bio‐composition and Morpholmentioning
confidence: 97%
“…Both TNF‐alpha and IL1‐beta were similar between exercised and control groups. Yet, significant differences were observed for IL‐4, IL‐6, and lubricin . Musumeci et al demonstrated that moderate physical activity improved lubricative properties of articular cartilage by promoting lubricin synthesis and its increase in the SF in adult (12 months old) and elderly (24 years old) rats compared to the unexercised group.…”
Section: The Exercise Effect On Cartilage Bio‐composition and Morpholmentioning
confidence: 99%
See 2 more Smart Citations
“…This will be the major cause of morbidity and physical limitation among individuals aged over 40 years (24). Current therapy for OA is directed toward non-pharmacological treatments as physical activity through mechanical stimulation (25) and symptomatic treatment, focusing in pain management, and is not able to promote regeneration of degenerated cartilage or to attenuate joint inflammation (18).…”
Section: Articular Cartilage and Inflammationmentioning
confidence: 99%